Effectiveness of different bio-fertilizers on growth, yield, and yield attributing characters of faba bean (Vicia fabae L.) - Mohammed Mebrahtu Mossa; Daniel Gebrekidan; Etsay Mesele; Melaku Mekonen Kasegn (Discover Agriculture)
Abstract The excessive use of chemical fertilizers has led to soil depletion of essential minerals, causing microorganisms to be distracted and reducing the distribution of soil fauna and flora. The field experiment examined the impact of biofertilizer (Rhizobium and Phosphorus Solubilizing Bacteria) and blended fertilizer (NPKSZn) on the growth, yield, and yield-attributing characteristics of faba bean. The experiment was laid out in RCBD with eight treatments. The result revealed that the application of biofertilizer significantly (P < 0.05) affected the growth and yield characteristics of faba bean. The longest grain filling period (51.42 days), tallest plant height (148.2 cm), Maximum nodulation (79.58), number of branches (6.42), pod per plant (34.08), highest thousand seed weight (699.9 g), grain (2369 kg ha−1), and biological yield (3942 kg ha−1), and the lowest chocolate spot disease severity index (13.33%) was noticed in dual inoculation of Rhizobium and PSB along with recommended dose of NPKSZn in both growing seasons. The highest net benefit (48,174.9 Ethiopian Birr (ETB) per ha) with an acceptable maximum marginal rate of return (789.26%) was recorded in dual inoculation of seed with Rhizobium and PSB. Therefore inoculations of Rhizobium and PSB enhance the production and productivity and reduce the chocolate spot infestation level. Hence the seed must be inoculated with a dual culture of Rhizobium and PSB along with another package of practices for the crop.